Virtual reality in the classroom: geography teaching practice - Trindade, Matheus José dos Santos; Santos, Cristiano Aprígio dos (Geosaberes; Vol 10 No 22 (2019): Sept - Dec, 2019)
21st century society is marked by technological advances. They transform and alter social relations in spacetime, especially in the work category. And considering the explosion of the use of Virtual Reality - technology that simulates real reality emerging who uses it in an immaterial reality - in several areas. We may ask: how important is the use of Virtual Reality (VR) technology in the teaching of geography? The aim of this study is to analyze the socio-educational effects of using VR technology as a didactic resource for the practice and teaching of geography. For didactic production we work the social and environmental conflicts and what it is to be indigenous in Brazil in the 21st century. Among the results stand out greater engagement and empathy for content and geographical science.